دوافع التعرض للإنتاج التلفزيوني الجزائري في القنوات الفضائية الجزائرية دراسة ميدانية على عينة من طلبة جامعة الوادي - رميصاء بن علي; منال بن خليفة (جامعة الوادي - University of Eloued, 2025)
"هدفت هذه الدراسة إلى التعرّف على دوافع التعرّض للإنتاج التلفزيوني الجزائري في القنوات الفضائية الجزائرية. وقد قمنا بدراسة ميدانية على عينة من طلبة جامعة الشهيد حمه لخضر الوادي وقد اعتمدنا الدراسة على المنهج المسحي لأنه يهدف إلى مسح الظاهرة موضوع الدراسة ويهتم بجمع البيانات والمعلومات وتم استخدام أداة الاستبيان كوسيلة لجمع المعلومات المتعلقة بموضوع الدراسة وقد قُدرت العينة بـ (128) طالبا وطالبة بجامعة الوادي، تم اختيارهم للإجابة على أسئلة الاستبيان وقد أسفرت الدراسة إلى : - تَبيّن أن الدافع المعرفي يأتي في مقدمة الدوافع التي تُحرّك الطلبة لمتابعة الإنتاج التلفزيوني الجزائري. - حلّ الدافع الترفيهي في المرتبة الثانية، مما يشير إلى أن الطلبة يبحثون أيضًا عن المتعة والتسلية من خلال هذه البرامج. - جاءت الدوافع الاجتماعية في مرتبة متأخرة، ما يدل على أن الطلبة لا يتابعون هذه البرامج بشكل أساسي لأجل التفاعل الاجتماعي أو الثقافي . " This study aimed to identify the motives for exposure to Algerian television production on Algerian satellite channels. We have conducted a field study on a sample of students of the University of Martyr Hama Lakhdar Al-Wadi The study has relied on the survey method because it aims to survey the phenomenon under study and is interested in collecting data and information and the questionnaire tool was used as a means of collecting information related to the subject of the study The sample was estimated at (128) male and female students at Wadi University, who were selected to answer the questionnaire questions, and the study resulted in: It turns out that cognitive motivation comes at the forefront of motivations that motivate students to follow Algerian television production. The recreational motivation came in second, suggesting that students are also looking for fun and entertainment through these programs. Social motivation ranked behind, indicating that students do not pursue these programs primarily for social or cultural interaction.
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: القنوات الفضائية الجزائرية; الإنتاج التلفزيوني; دوافع التعرض; Motives; New production; Algerian television channels